«Արձագանգ» ամսաթերթի մասին - Խաչատրյան, Մարգարիտա (Հայաստանի ազգային գրադարան)
From 1672 to 1976 in Toronto the AYF “Simon Zavarian” chapter published the “Ardzagank” (Echo) monthly newspaper. The 58 issues were presented in 48 volumes: 8 volumes had two issues and one had 3 issues. Many exceptional articles were published in this monthly, which can still interest not only the readers but also the specialists dealing with issues of the Armenian Diaspora and the press. The rich material presented in this monthly is the diary of five years of the lives of Armenians in Toronto. Many names were immortalized on the pages of “Ardzagang.” Due to their efforts and devotion the publication of the newspaper was realized without paid subscription and sizable financial means. The literary pieces were chosen meticulously from Mesrop Mashtots to Paruyr Sevak, materials representing prominent figures of the world culture and Diaspora, book reviews, interpretations of interesting aspects of local and Armenian life. All issues of the monthly newspaper are notable for their rich content.
Keywords: Սփյուռքի ժառանգության պահպանություն